Performativities of intimacy in the age of biopolitics - Novati, Gabriella Calchi (Trinity College (Dublin, Ireland). Department of Drama, 2012)
The aim of this thesis is to propose a dialogue between Giorgio Agamben’s philosophy and the field of 'performance studies'. My theory of the performativity of intimacy needs to be read as a conceptual attempt to address that which performs in the current crisis of community and the resulting loss of a common polis. Far from being a philosophical treatise, this thesis is nonetheless a theoretical piece. In agreement with Agamben's main claim that life in our contemporaneity is caught in a state of indistinction, such an indistinction, I advance, could be envisioned as residing in- between what Diana Taylor calls the archive (i.e. text) and the repertoire (i.e. spoken language). In the wake of Richard Schechner's main idea, namely, that a performance studies scholar examines anything "as" performance, whether it be a text, a video¬installation or a photograph, the elements that comprise my study are to be considered 'practices' or 'events'. The chapters of this thesis, at first, might be mistakenly read as individual unities about individual objects, perhaps even unrelated to each other. The term mistakenly is employed here following Spivak: mistake as a way of reading that, in an attempt to grasp the repertoire, gets lost in the archive. The individual sections of this thesis provide the score of my theoretical proposition, so as to allow movement from the archive to the repertoire. For music to exist, a performance needs to take place, since the written musical score is, in itself, silent and indeed very different from the performed musical piece. Therefore, in my thesis, I start firstly with a personal prelude, which then moves into a more rigorous overture, at the end of which the actual symphony of thoughts occurs.
Keywords: Drama, Ph.D.; Ph.D. Trinity College Dublin